IMPLEMENTASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) DI KOTA SEMARANG - Herbasuki Nurcahyanto (GEMA PUBLICA : Jurnal Manajemen dan Kebijakan Publik, 2016)
Poverty is a main issue tosolve. National Urban Program for People Empowerment (PNPM MP) has main program to alleviate poverty by involving participation of the villagers. The purpose of the  research is to analyze the implementation and identify the inhibiting factors of PNPM MP, in Mangunharjo residence Tembalang District Semarang. The approach used is descriptive qualitative approach. The implementation of PNPM MP in Mangunharjo was started in 2007. Direct People Assistance (Bantuan Langsung Masyarakat/BLM) received are used to alleviate poverty through three areas: economy, social and environment. Self-Assistance Groups (Kelompok Swadaya Masyarakat/KSM) has easy access to obtain additional capital to run a business. Poor villagers are asissted through house rehabilitation program and education package. The negative Impacts  also come up that there is  social envy especially for those who do not receive the assistance. The inhibitting factors of the implementation of PNPM MP in Mangunharjo Residence include the internal factors: The limited number of the operating unit members, Some BKM members are not active in some activities, The KSM members do not have sufficient skill to arrange the proposal. While the external factors include: the distrust of villagers toward the credibility of KSMmembers to implement physical projects, and the envy shown by those who do not get  BKM. To increase the awareness of the BKM and KSM members are through trainings, assistingKSM to prepare the project proposals and eventhe reports regularly and continuously. There should be a socialization to the villagers about the programs managed by BKM through regular meetings of RT / RW or the engagement of the community leaders to take a part routinely in the annual meeting forum of  the villagers (Rembug Warga Tahunan/RWT).